Synergistic effect of modified pore and heterojunction of MOF-derived α-Fe2O3/ZnO for superior photocatalytic degradation of methylene blue. Issue 6 (26th January 2023) - Zulfa, Liyana Labiba; Ediati, Ratna; Hidayat, Alvin Romadhoni Putra; Subagyo, Riki; Faaizatunnisa, Nuhaa; Kusumawati, Yuly; Hartanto, Djoko; Widiastuti, Nurul; Utomo, Wahyu Prasetyo; Santoso, Mardi
Abstract : Mesoporous heterojunction MOF-derived α-Fe2 O3 /ZnO composites were prepared by a simple calcination of α-Fe2 O3 /ZIF-8 as a sacrificial template. Abstract : Mesoporous heterojunction MOF-derived α-Fe2 O3 /ZnO composites were prepared by a simple calcination of α-Fe2 O3 /ZIF-8 as a sacrificial template. The optical properties confirm that coupling of both the modified pore and the n–n heterojunction effectively reduces the possibility of photoinduced charge carrier recombination under irradiation. The mesoporous Fe(25)ZnO with 25% loading of α-Fe2 O3 exhibited the best performance in MB degradation, up to ∼100% after 150 minutes irradiation, higher than that of pristine ZnO and α-Fe2 O3 . Furthermore, after three cycles reusability, mesoporous Fe(25)ZnO still showed an excellent stability performance of up to 95.42% for degradation of MB. The proposed photocatalytic mechanism of mesoporous Fe(25)ZnO for the degradation of MB corresponds to the n–n heterojunction system. This study provides a valuable reference for preparing mesoporous MOF-derived metal oxides with an n–n heterojunction system to enhance MB photodegradation.